Jerome S. Bruner Cognitive Development Theory - Dewa Ayu Juli Damayanti; Agus Dita Saputra; I Wayan Darmika Yana; Basilius Redan Werang (International Journal of Education, Vocational and Social Science, 2025)
Jerome S. Bruner’s theory of cognitive development views learners as active builders of their own understanding. He argues that learning is a personal process, deeply influenced by social interaction, hands-on experience, and language. Central to his ideas are discovery learning, the spiral curriculum, and the three modes of knowledge representation—enactive, iconic, and symbolic. According to Bruner, education should encourage students to explore, discover, and reflect for themselves. His approach remains highly relevant today, aligning with the 21st-century emphasis on critical thinking, creativity, and independent learning.